P 66 Prognostic properties of electroencephalographic patterns on overall, short- and long-term mortality in patients with hypoxic encephalopathy after cardiopulmonary resuscitation. (May 2022) - Willems, L.M.; Trienekens, F.; Knake, S.; Beuchat, I.; Rosenow, F.; Schieffer, B.; Karatolios, K.; Strzelczyk, A.
Abstract : Introduction: Hypoxic encephalopathy (HE) is a common neurological condition on intensive care units (ICUs) after initially successful cardiopulmonary resuscitation (CPR) following cardiac arrest (CA) or after other life-threatening conditions associated with transient hypoxia. For both clinicians and relatives or caregivers of affected patients, HE is very challenging as assessing the individual prognosis of HE seems difficult. There has been repeated evidence of the diagnostic benefit of early electroencephalographic (EEG) evaluations, proposing a predictive potential of different EEG patterns in terms of therapeutic outcome and estimation of mortality. The aim of this study was to investigate the prognostic properties of distinct EEG patterns during acute care with overall, short-term, and long-term mortality in HE patients. Patients and Methods: This analysis is based on a retrospective, monocenter study enrolling all adult patients with confirmed HE after CPR and prolonged or inadequate wake-up response between January 2011 and June 2005. All patients were managed according to current national and international guidelines on post-CPR care. Neurological examinations and EEGs were performed in normothermia and after a minimum of 24-hour sedative-free intervals. All EEGs were rated by two independent EEG specialists following the current recommendations of the American Society of Clinical Neurophysiology (ACNS) on ICU EEG terminology. Correlation of EEG patterns with overall, short-term, i.e., deceased during acute care or within the first 30 days after hospital discharge, and long-term mortality, i.e., deceased later than 30 days post discharge, were accessed using univariate log-rank test (LR) and multivariate cox regression analysis (MCA). Results: A total of 199 patients were included in the final analysis. In-hospital mortality was 47.7%. Short-term mortality was 54.8%, long-term mortality was 69.8%, 71.9% and 72.9% at 12, 24 and 36 months respectively. LR revealed a significant association between EEG suppression (SUP) and short-term mortality, and identified low voltage EEG (LV), burst suppression (BSP), periodic discharges (PD) and post-hypoxic status epilepticus (PSE) as well as missing (aBA) or non-reactive background activity (nrBA) as predictors for overall, short- and long-term mortality. MCR indicated SUP, LV, BSP, PD, aBA and nrBA as significantly associated with overall and short-term mortality to varying extents. LV and BSP were significant predictors for long-term mortality in short-term survivors. Rhythmic delta activity, stimulus induced rhythmic, periodic, or ictal discharges and sharp waves were not significantly associated with a higher mortality. Conclusion: Early EEG after CPR can help to predict short- and long-term mortality in HE patients. Besides EEG background activity and reactivity to stimuli, the presence of several specific EEG patterns has a distinct prognostic property.